Factors influencing inferior vena cava diameter and its respiratory variation: Simultaneous comparison with hemodynamic data. Issue 5 (May 2022) - Kawata, Takayuki; Daimon, Masao; Nakanishi, Koki; Kimura, Koichi; Sawada, Naoko; Nakao, Tomoko; Hirokawa, Megumi; Ishiwata, Jumpei; Takeda, Norifumi; Yatomi, Yutaka; Komuro, Issei
Highlights: To recognize factors other than right atrial pressure (RAP) that may influence inferior vena cava (IVC) measurements is critical. Significant tricuspid regurgitation, larger body surface area, and younger age are associated with the IVC distension. In contrast, IVC collapsibility index is influenced only by RAP. Abstract: Background: Ultrasound assessment of inferior vena cava (IVC) diameter and its respiratory variation is widely used to estimate right atrial pressure (RAP). Generally, the IVC distends as the RAP rises; however, there may be discrepancies between the values. Therefore, it is critical to recognize clinical factors other than RAP that may influence IVC measurements. Methods: We obtained the IVC maximum diameter and IVC collapsibility index (IVCCI) simultaneously during right-heart catheterization in 71 consecutive patients. Then, we assessed various clinical and hemodynamic factors to elucidate the independent determinants of IVC measurements. Moreover, we tried to generate the regression equation to estimate mean RAP from the IVC maximum diameter and IVCCI. Results: The mean IVC maximum diameter and IVCCI were 15 ± 4 mm and 51 ± 15%, respectively. In stepwise multivariate analysis, the higher mean RAP (β = 0.52; p  < 0.0001), the presence of significant tricuspid regurgitation (β = 0.31; p  = 0.0005), a larger body surface area (β = 0.22; p  = 0.0017), and younger age (β = -0.18; p  = 0.049) were independently associated with the IVC maximum diameter. Only the mean RAP was independently associated with the IVCCI (β = -0.45; p  < 0.0001). The regression equation (R 2  = 0.43, p  < 0.0001) was as follows: estimated mean RAP = 3.7 + 0.62 × maximum IVC diameter / BSA - 0.07 × IVCCI. Conclusion: Distension of the IVC mainly occurs with elevated RAP. However, the presence of significant tricuspid regurgitation, a larger body surface area, and younger age are associated with the IVC maximum diameter, independently of RAP. Interestingly, IVCCI is influenced only by RAP. Graphical abstract: Image, graphical abstract